Development and initial validation of the Role Strain Questionnaire for Junior Athletes (RSQ-JA). (May 2016) - van Rens, Fleur E.C.A.; Borkoles, Erika; Farrow, Damian; Curran, Thomas; Polman, Remco C.J.
Abstract: In a series of related studies, the relevance of a role strain framework to interpret the difficulties junior elite athletes experience in their multiple life domains was assessed. Here, the Role Strain Questionnaire for Junior Athletes (RSQ-JA) was developed to measure the role strain experienced by junior athletes. In Study 1, role strain was explored via interviews with 20 elite junior athletes. Based on themes emerging from these interviews, an initial 65-item pool for the RSQ-JA was created and subjected to an exploratory factor analysis in Study 2. The factors derived in Study 2 were tested for factorial validity using confirmatory factor analysis in Study 3. Results supported a 22-item five factor structure for the RSQ-JA. These factors reflected the salient sources of role strain, namely; (i) overload in school, (ii) overload in sport and between roles, (iii) between-role conflict, (iv) underload, and (v) ambiguity. The RSQ-JA therefore provides the initial validation of the first measure of role strain experienced by junior elite athletes. Highlights: Junior elite athletes experience role strain in their dual careers. The Role Strain Questionnaire for Junior Athletes (RSQ-JA) was developed. Initial validation of the RSQ-JA shows that the scale has promising psychometric properties. Experiences of overload in sport and between roles are associated with increased stress.